The Paradox of Punishment: Between Assimilation and Indonesian Public Health During the Covid-19 Pandemic - Putu Bagus Satya Nugraha; I Nyoman Bagiastra (Westscience Press, 2023)
Since the beginning of 2020, Indonesia has been hit by a deadly virus outbreak known as Corona Virus Disease or Covid-19. Covid-19, which is claimed to be a pandemic, has changed the foundations of all sectors of life, including the legal and criminal system in Indonesia. Various gaps have been created between das sein and das sollen related to the regulations issued by the government to reduce the number of Covid-19 cases. On the one hand, the Ministry of Law and Human Rights in its mandate has established a policy of releasing prisoners through the assimilation and integration rights program as one of the steps to suppress the spread of Covid-19. Contrary to this, on the other hand, a regulation has emerged that threatens the public for those who violate the rules regarding the prevention of this epidemic, especially for violators of Law Number 6 of 2018 concerning Quarantine. These two law enforcement policies will certainly be a punishment paradox where if prisoners are given assimilation, it will have the potential to cause a Covid-19 cluster from prisons to the general public and also has the potential to cause other problems such as committing crimes again. Likewise, if a prokes violator is put in prison, it is possible that he will contract Covid-19 and spread it to prisoners in prison, so this will become very vulnerable considering that the number of prisoners in prison is very large and even over capacity.